The Recurrencies, in operated cancer of rectum: a series of 166 cases - Praderi, Luis A; Balboa, Oscar; Voelker, Ricardo; Pittamiglio, Héctor; Pizzarrossa, Carlos (Cirugía del Uruguay, 1979)
Review of tumor recurrencies in a series of 166 patients operated of neoplasms of rectum, with reference to etiopathogeny, clínica! syndrcmes, early diagnosis nnd treatment.